Endovascular Sharp Recanalization for Calcified Femoropopliteal Artery Occlusion - Hsuan-Li Huang; Hsin-Hua Chou; Tien-Yu Wu (Case Reports in Cardiology)
Endovascular intervention of peripheral chronic total occlusion (CTO) is technically challenging and time consuming. Various techniques and devices are used to facilitate lesion crossing and improve the success rate of the procedure. However, these new devices are quite expensive and not readily available. We report 2 cases of peripheral CTO wherein the occlusions were successfully crossed by using stiff end of Terumo glidewire. This sharp recanalization may be a useful technique for the recanalization of calcified peripheral CTOs when conventional techniques fail and new devices are not readily available, but it is accompanied by the risk of distal atheroembolism.